SIFAT PEMESINAN 32 JENIS KAYU DARI DAERAH JAWA BARAT DAN NUSA TENGGARA TIMUR - Osly Rachman (Jurnal Penelitian Hasil Hutan, 1988)
The paper presents  a  test result of machining properties  of 32 wood species from  West Java  and East of Nusa  Tenggara East. The air dried samples were tested according  to  the ASTM  D1666/64 standard  that was modified  according  to the Forest Products Research Institute  Report  No. 160  (1982).   In most  of the species 25 or more samples were available  for  test.  The machining  properties   tested  included  planning,  shaping, boring,  turning  and sanding.The  result  reveals  that  eighteen  wood  species have good  to  very good machining   properties, five  species  have  very good  machining  properties namely gintung, pongokan,    rasamala, melur,  tanjung  and leda  II.The  other  species are  good  or fair in some  properties  and poor  or very poor  in other.  The species with poor  or very poor   machining  properties   are  bareuhbeuy, hantap heulang  and  leda   III.